2014
DOI: 10.1007/s11695-014-1322-y
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transesophageal Gastro-tubing for Management of Gastric Leakage After Sleeve Gastrectomy

Abstract: Gastric leakage is a challenging complication of sleeve gastrectomy. Multimodal approaches, including drainage, clipping, and stenting of the leak, are occasionally insufficient. We report successful management of refractory gastric leakage using percutaneous transesophageal gastro-tubing (PTEG). Drainage and stenting proved inadequate for treating sleeve leakage near the esophagogastric junction in two patients. PTEG was finally performed, and enteral feeding was started on the following day. The patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Long-term use of an NGT causes poor patient tolerability and complications, including epistaxis, aspiration pneumonia, and sinusitis. Oshiro et al have reported PTEG for the management of gastric leakage after sleeve gastrectomy [24]. For patients who underwent bariatric surgery, it is challenging to re-operate for anastomotic leakage because of the patients' risk, i.e., they are highly obese and therefore have many preoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of an NGT causes poor patient tolerability and complications, including epistaxis, aspiration pneumonia, and sinusitis. Oshiro et al have reported PTEG for the management of gastric leakage after sleeve gastrectomy [24]. For patients who underwent bariatric surgery, it is challenging to re-operate for anastomotic leakage because of the patients' risk, i.e., they are highly obese and therefore have many preoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…In our center, all of the leaks from all sleeve cases in the past 8 years, whether performed at our center or outside centers and then transferred to our care, occurred in the proximal 4 cm or less of the sleeve. A high percentage of the published cases occur at this location [58]. Contributing factors include tissue ischemia, elevated intraluminal pressures, host impaired healing, and suboptimal closure techniques including poor stapler height choice, staple malformation, or hematoma formation.…”
Section: Discussionmentioning
confidence: 99%
“…Small-bowel tubing via the PTEG route is a feasible procedure to relieve nasal discomfort. 13,14 Post-esophagectomy Generally, PTEG is not indicated after esophagectomy because percutaneous gastrojejunostomy is technically feasible. 15 However, percutaneous gastrojejunostomy is also technically difficult for subtotal esophagectomy with a gastric tube reconstruction of the posterior mediastinal route.…”
Section: Gastrointestinal Tubing Via the Percutaneous Transesophageal Gastrotubing Routementioning
confidence: 99%